Corrosion product transformations in alkaline baths under pressure and high temperature: The sub‐critical stabilisation of marine iron artefacts stored under atmospheric conditions. Issue 2 (8th October 2015) - Bayle, M.; de Viviés, P.; Memet, J.‐B.; Foy, E.; Dillmann, P.; Neff, D.
Abstract : In the context of conservation of ferrous cultural heritage, dechlorination processes of archaeological iron artefacts are studied in subcritical conditions which consist of immerging an artefact inside an alkaline bath under pressure (30 bar) and temperature (160 °C). Submarine archaeological environments lead to the presence of chlorides inside the corrosion layers. After exposure to the atmosphere following excavation, initial corrosion phases evolve. Chlorides remain trapped inside the structure of corrosion products particularly during the crystallisation of akaganeite. Stabilisation treatment objectives are to remove chlorides from the corrosion layers and to obtain more stable phases. A Roman archaeological bar has been studied on cross‐section before and after treatment in sub‐critical conditions. Less stable phases, such as ferrihydrite and akaganeite, transformed into hematite. That was confirmed by the use of synthetic and pure phases treated in the same conditions. The presence of goethite before and after the treatment in the corrosion profile raises the question of its reactivity during dechlorination process. Akaganeite has been synthesised and compared to archaeological powder sampled on an artefact. The results highlight reactivity differences indicating that sub‐critical transformation processes are not only dependent on the nature of phases but also on intrinsic physical characteristics.